(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Ankylosing spondylitis (AS) is chronic inflammatory disorders of unknown cause that primarily affects the axial skeleton (Predominantly sacroiliac joints and spine) peripheral joints and of extra articular structures may also be involved in an asymmetrical pattern. The disease usually begins in the second or third decade; the male to female prevalence is approximately 3:1. Patients having AS, more than 95% of them are positive HLA-B27. Use of NSAIDS are the first line of management and they effectively relieve the symptoms. Few Ayurvedic medicines found to be effective in the management of AS. Here, a case study of AS managed by Ayurvedic treatment approaches is presented. A patient 21yrs male came to OPD of Kayachikitsa i.e., Room No. 9 of GACH, Patna. He complaint of pain in B/L ankle left>right, also B/L knee joint pain as well as low back pain for 6 months. He was diagnosed on the basis of its signs and symptoms of AS with HLAB27 positive. He was managed by Ayurvedic medicines like Panchatikta Ghruta Gugglu, Ekangveer ras, Tab. Shallaki, Cap. Stresscom, Jrumax oil, Vaishwanar churna, Laxarid for 7 months and relief in his signs and symptoms.